Anti‐Inflammatory Oxicams as Multi‐donor Ligand Systems: pH‐ and Solvent‐Dependent Coordination Modes of Meloxicam and Piroxicam to Ru and Os. Issue 20 (21st March 2017) - Aman, Farhana; Hanif, Muhammad; Kubanik, Mario; Ashraf, Adnan; Söhnel, Tilo; Jamieson, Stephen M. F.; Siddiqui, Waseeq Ahmad; Hartinger, Christian G.
Abstract: The nitrogen‐ and sulfur‐containing 1, 2‐benzothiazines meloxicam and piroxicam are widely used as nonsteroidal anti‐inflammatory drugs. Intrigued by the presence of multiple donor atoms and therefore potentially rich coordination chemistry, we prepared a series of organometallic Ru and Os compounds with meloxicam and piroxicam featuring either as mono‐ or bidentate ligand systems. The choice of the solvent and the pH value was identified as the critical parameter to achieve selectively mono‐ or bidentate coordination. The coordination modes were confirmed experimentally by NMR spectroscopy and single crystal X‐ray diffraction analysis. Using DFT calculations, it was established that complexes in which meloxicam acts as a bidentate N, O donor are energetically more favorable than coordination as O, O and S, O donor systems. Since meloxicam and piroxicam derivatives have shown anticancer activity in the past, we aimed to compare the complexes with mono‐ and bidentate ligands on their in vitro anticancer activity. However, stability studies revealed that only the latter complexes were stable in [D6 ]DMSO/D2 O (5:95) and therefore no direct comparisons could be made. The meloxicam complexes1 and2 showed moderate cytotoxicity, whereas the piroxicam derivatives5 and6 were hardly active against the utilized cell lines. Abstract : How do they bind ? The intriguing coordination properties of the nitrogen‐ and sulfur‐containing 1, 2‐benzothiazines meloxicam and piroxicam were established to organometallic Ru and Os centers with meloxicam and piroxicam featuring either as mono‐ or bidentate ligand systems. The choice of the solvent and the pH value was identified as the critical parameter to achieve selectively mono‐ or bidentate coordination.